Hyaluronic Acid-based Filler Injection: Late-onset Thrombosis of the Frontal Vein. Issue 11 (November 2020) - Gabrielpillai, Jennis; Salamat, Arash; Schaefer, Christian; Kania, Alexander; Lunatschek, Christian; Eichhorn, Klaus Wolfgang; Bootz, Friedrich; Send, Thorsten
Abstract : Summary: Thrombosis is a serious complication of a hyaluronic acid-based filler injection. Little is known about the late-onset complications of fillers; therefore, an optimal complication management is necessary. In this case report, we describe a rare complication of thrombosis after a filler injection. A 35-year old woman was admitted to the emergency department, with swelling on her forehead in association with recurrent pain and light flashes in her right eye. Sonographic examination showed a thrombosis of the right frontal vein. The patient reported that a hyaluronic acid filler injection had been administered on the forehead 3 months ago. After several weeks of anticoagulation with heparin and apixaban, the symptoms persisted. The vein with thrombosis was ultimately resected under local anesthesia. Histological findings showed a chronic inflammatory reaction of the tissue to hyaluronic acid. Vascular complications may appear as late-onset complications even several months after the filler injection. Subcutaneous application of low molecular weight heparins is the therapy of first choice. If this treatment is not effective, resection of the thrombosis may be performed.